ChemInform Abstract: A Novel Paradodecatungstate‐B Compound Decorated by Transition Metal Copper, Na2Cu5(H2O)24(OH)2 [H2W12O42]·10H2O: Synthesis, Structure and Antitumor Activities. Issue 44 (15th October 2015) - Qu, Xiaoshu; Yang, Yanyan; Yu, Xiaoyang; Lv, Ze; Ji, Mingshuang; Feng, SuYang
Abstract The title compound is prepared by evaporation of an aqueous solution containing Na2WO4, H2SO4, CuSO4, morpholine, AcOK, and HCl (pH 3.8, room temperature, 7 d, 29% yield).